Burnout among EFL Teachers in Indonesia: Prevalence, Triggers, and Strategies - Lilis Khopifah; Nurul Faadhilati Idris; Tsarwan Kasyfillah Nasution; Reza Anis Maulidya (Universitas Islam Negeri Palopo, 2025)
This study investigates the prevalence, triggers, and coping strategies related to burnout among English as a Foreign Language (EFL) teachers in Indonesia. Using a mixed-methods design, data were collected through a survey of 50 EFL teachers and follow-up interviews with 10 participants. Findings from the adapted Maslach Burnout Inventory–Educators Survey (MBI-ES) reveal moderate emotional exhaustion (45%), low depersonalization (17%), and lower levels of personal accomplishment (33%). Guided by the Job Demands–Resources (JD-R) and Conservation of Resources (COR) frameworks, the study identifies key burnout triggers, including academic pressures (85%), emotional demands (84%), organizational factors (77%), and economic concerns (78%). Despite experiencing emotional strain, teachers generally maintain stable instructional performance, reflected in consistent lesson delivery and classroom management. To cope with burnout, teachers primarily rely on personal well-being routines, social support, and self-management strategies, while institutional support remains limited and inconsistent. Overall, the findings underscore the need for stronger systemic and organizational support to enhance teacher well-being and sustain effective EFL instruction in Indonesia.